Application of accounting tools in Polish hospitals - Magdalena Kludacz-Alessandri (Zeszyty Teoretyczne Rachunkowości, 2016)
Accounting policy is defined as a set of rules and methods for estimating conventional values, and proce-dures regarding the presentation of financial statements. It can also be used for determining the value of assets and financial results in financial statements to help in achieving specific goals of the entity. The aim of the article is to analyze the degree of use of selected instruments of accounting policy in Polish hospitals. The main attention was paid to the instruments of material accounting policies. The first partof the paper uses the method of literature studies. It describes the essence of accounting policy and triesto provide an explanation of existing differences between the terms balance sheet policy and account-ing policy because there are at least a few perspectives on their meaning and their relations with each other. The second part of paper presents the results of an empirical study conducted in 2012-2013 in selected Polish hospitals. The study involved managers of hospitals that responded to questions regarding the use of selected instruments of material accounting policies in shaping the information content of financial statements for the purpose of achieving the objectives of the entity. The research showed that Polish hospitals do not apply (or apply to a limited extent) the instruments of accounting policy to support the management process. In most of cases, the managers are not interested in accounting policy in general, and they are not interested in its impact on the content of the financial statements of the hospital.